Research on 5G banking industry private network solution - Yafeng WANG; Chunhua LIANG; Lanlan ZHU; Xiaoping WANG (Dianxin kexue)
At present, China is in the wave of new infrastructure construction.It had become an industry consensus to accelerate the construction of new information infrastructure resources such as 5G and computing resources, and then it was integrated with advanced technologies such as AI and big data to promote the high-quality development of China’s digital economy.As the main force of the digital economy, the banking industry urgently need to vigorously develop financial technology and explore intelligent transformation.Based on the industry pain points of the banking industry, combined with the urgent needs of customers in the banking industry, five business scenarios were sorted out including AI passenger flow insight and 5G+XR immersive marketing, and the key issues of planning and networking in the banking industry based on the above five business scenarios were summarized.It will help to construct of the industry’s 5G private network and successfully realize the digital and intelligent transformation of China’s banks.